Assessment of Energy Wood Resources in Northwest Russia - Gerasimov, Yuri; Karjalainen, Timo (Finnish Forest Research Institute, 2009)
The energy wood procurement possibilities for the eight regions making up Northwest Russia were assessed. Wood byproducts from roundwood harvesting and sawmilling were considered for energy production based on actual harvesting, sawmill and plywood production figures for 2006. Of the total calculated potential of 31 million solid m3 (62 TWh), nearly 70% (21.8 million m3) is from harvesting. The remainder (9 million m3) is from saw and plywood milling. The approximate available energy wood by region would be: 2.3 million m3 from the Republic of Karelia, 2.7 million m3 from the Republic of Komi, 5.4 million m3 from Arkhangelsk, 4.6 million m3 from Vologda, 3.8 million m3 from Leningrad, 2.0 million m3 from Novgorod, 0.8 million m3 from Pskov, and 41,000 m3 from the Murmansk regions. There are large differences in the potentials between and within the regions. This is due to the differences in their forest resources; differences in their utilisation of these resources; the available intrastructures; some limitations on wood harvesting. A part of this calculated potential is already utilised, since some non-industrial roundwood from central processing yards sawmills and plywood mills are currently used in energy production. Nearly 65% of all the potential energy wood from roundwood harvesting is non-industrial roundwood, 19% is spruce stumps removed after final felling, 8% is unused branches and tops, and 8% is defective wood resulting from logging. About 58% of the total potential energy wood from roundwood harvesting is coniferous. However, there are large differences between the regions and within the regions in the species proportions. Currently about 40% of the allowable cut is used. This means that it would be possible to intensify the utilisation of the forest resources and thereby also to increase the use of wood for energy production. Full implementation of the allowable cut could provide 73.5 million m3 of energy wood (147 TWh). In addition, if the technical potential for thinnings was utilised, the total potential energy wood provided by roundwood harvesting, saw and plywood milling could be 104 million m3 (208 Twh).
Keywords: energiapuu; hakkuutähteet; puunhankinta; energy wood; logging residues; non-industrial roundwood; wood procurement